Microfluidics on standard Petri dishes for bioscientists - Deroy, C; Nebuloni, F; Cook, PR; Walsh, EJ (Wiley, 2021)
Few microfluidic devices are used in biomedical labs, despite the obvious potential; reasons given include the devices are rarely made with cell-friendly materials, and liquids are inaccessibly buried behind solid confining walls. An open microfluidic approach is reviewed in which aqueous circuits with almost any imaginable 2D shape are fabricated in minutes on standard polystyrene Petri dishes by reshaping two liquids (cell-culture media plus an immiscible and bioinert fluorocarbon, FC40). Then, the aqueous phase becomes confined by fluid FC40 walls firmly pinned to the dish by interfacial forces. Such walls can be pierced at any point with pipets and liquids added or removed through them, while flows can be driven actively using external pumps or passively by exploiting local differences in Laplace pressure. As walls are robust, permeable to O2 plus CO2, and transparent, cells are grown in incubators and monitored microscopically as usual. It is hoped that this simple, accessible, and affordable fluid-shaping technology provides bioscientists with an easy entrée into microfluidics.